(untitled) (Annals of Medical Research, 2021)
Aim: The aim of the study is to investigate the effect of different surface treatments applied to the fiber reinforced composite post surface on post-dentin connection. In addition, bond strengths of post in cervical and apex regions have also been checked.Material and Methods: Central upper teeth were used for the study, various surface treatments (50 µm aluminium particles, Er: YAG laser. Primer, Cojet) were conducted on the post surface except control group. Accordingly, samples were randomly divided into 5 groups (50 µm aluminium particles, Er: YAG laser. Primer, Cojet and control groups) as being 10 in each group. Following these treatments, dentin bonding agents were applied to root canal and light was practiced for 20 seconds. Next, resin composite was placed on the surfaces of posts and it was cured with light for 40 seconds from 2 mm away of post cavity.Results: It was observed that there was high bond strength in Al2O3 group. A significant difference was not determined between push-out bond strength of apex regions of all groups. Conclusion: It was seen that the samples in the group where aluminum particles were applied showed highest bond strength and laser group followed this. It was also seen that there was higher bond strength in cervical region compared to apex.